Optimizing Anterior En Masse Retraction with Miniscrew Anchorage - Pavankumar Janardan Vibhute (Case Reports in Dentistry)
In severely protrusive patients, skeletal anchorage from miniscrew is often used to avoid anchorage loss with preferred miniscrew location near centre of resistance (Cres) of posterior teeth. Biomechanical requirement for directing retraction force towards Cres of posterior teeth demands the insertion of miniscrew in loose mucosa, where risk of infection and failure increases. In addition, undesirable biomechanical side effects on anterior and posterior segments may be possible in all three planes, when continuous arch sliding mechanics are installed with miniscrew anchorage. This paper describes technique of molar-stabilizing power arm (MSPA) for simultaneous intrusion and retraction of anteriors with miniscrew placement at attached gingiva between 1st molar and 2nd premolar. Advantages of this technique include (i) the need of miniscrews placement in loose mucosa apically near the Cres of the posterior teeth is eliminated, (ii) the risk of infection and miniscrew failure is lowered since the miniscrew is placed in attached gingiva rather than the loose mucosa, and (iii) by adjusting vertical length or replacing MSPA, alteration of the retraction force vector is possible in all three planes; thus, need of removal and repositioning of the miniscrew (e.g., in correction of occlusal cant) can be eliminated.